Analisis Implementasi Keadilan Sosial Pancasila Pada Populasi Anak Penyandang HIV/AIDS Di Yogyakarta - Moch Najib Yuliantoro; Rizky Anandasigit Nugraha; Aisyah Abbas; Rona Utami; Supartiningsih Supartiningsih (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2019)
HIV/AIDS (Human Immunodeficiency Virus / Acquired Immune DeficiencySyndrome) is one type of viral diseases that becomes a global issue.The number of people that have been infected by HIV in Yogyakarta in2017 reached 3,688 people and 1,468 of them had been diagnosedlived with AIDS.Most people living with the virus are in the productive age around 20– 24 years due to the risky sexual relations. Based on the report ofthe Daerah Istimewa Yogyakarta AIDS Commission, there was 428 peopleinfected with HIV and as many 141of those infected with AIDS were children under19 years old. This study identifiesproblemsof implementingthe concept of social justice in Pancasila amongchildren with HIV/AIDS inYogyakarta as a vulnerable group in Indonesia. This researchaims to understand the views of children with HIV/AIDS inYogyakarta about social justice through their lifeexperiences. It furtherreconstructs the concept ofPancasila social justice to see the consistency and inheritance bothin theory and practice. The research was carried out throughliterature studies, field studies, and in-depth interviews. Thisresearch is a preliminary study with a target sample of 10-15 childrenselectedpurposively according to their medical record for having HIV/AIDS and lived in Yogyakarta. The classification, analysis and interpretation of datawere employed to obtain a balanced, objective and a deeperunderstanding. The resultsof this study provide scholarly information about the theoreticalconstruction of the concept of Pancasila social justice, a map of theissue of the implementation of Pancasila social justice in childrenwith HIV/AIDS in Yogyakarta, and the views of children with HIV/AIDS on what social justice is.